The Business of iPhone App Development Making and Marketing Apps that Succeed - Wooldridge, Dave.; Schneider, Michael; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; et al. (Berkeley, CA : Apress, 2010)
The phenomenal success of the iPhone and the iPod touch has ushered in a (3z(Bgold rush(3y (Bfor developers, but with well over 100,000 apps in the highly competitive App Store, it has become increasingly difficult for new apps to stand out in the crowd. Achieving consumer awareness and sales longevity for your iPhone app requires a lot of organization and some strategic planning. This book will show you how to incorporate marketing and business savvy into every aspect of the design and development process, giving your app the best possible chance of succeeding in the App Store. The Business of iPhone App Development was written by experienced developers with business backgrounds, taking you step-by-step through cost-effective marketing techniques that have proven successful for professional iPhone app creators$1 (Bperfect for independent developers on shoestring budgets. Although there are a few iPhone app marketing books on the horizon, they appear to tackle the subject from purely a marketer$1 (Bs perspective. What makes this book unique is that it was written by developers for developers, showing you not only what to do, but also how to do it, complete with time-saving resources and ready-to-use code examples. No prior business knowledge is required. This is the book you wish you had read before you launched your first app!s
Seeing the Big Picture in a Crowded App Store Marketplace -- Doing Your Homework: Analyzing iPhone App Ideas and Performing Competitive Research -- Protecting Your Intellectual Property -- Your iPhone App Is Your Most Powerful Marketing Tool -- Money for Nothing: When It Pays to Be Free -- Exploring New Business Models with In-App Purchase and Affiliate Programs -- Testing and Usability: Putting Your Best Foot Forward -- Get the Party Started! Creating a Prerelease Buzz -- Keys to the Kingdom: The App Store Submission Process -- Increasing Awareness for Your iPhone App.
Keywords: Computer science; Data structures (Computer science).; Computer Science; Data Structures, Cryptology and Information Theory